Teaching Methods of Basic Life Support (Bls) and Their Effects on School Students’ Skills: A Literature Review - Putra, Satria Hanggara; Jasmin, Muh. (PT. Nursing Genius Care, 2026)
Background: Basic Life Support (BLS) is a series of emergency interventions performed to restore and maintain vital body functions in individuals experiencing cardiac arrest or respiratory arrest. Adequate knowledge and skills among school students are essential to ensure that first aid can be provided correctly and promptly, thereby preventing mortality. Purpose: This literature review aims to describe various effective teaching methods used in Basic Life Support (BLS) training for school students. Methods: This study employed a literature review method by searching relevant articles from three electronic databases: PubMed, Cochrane, and ScienceDirect. The search strategy was developed using the PICO framework. Inclusion criteria included articles published within the last 10 years, focusing on BLS training for school students aged 11–16 years, available in full text, written in English or Indonesian, and using a Randomized Controlled Trial (RCT) design. The PRISMA flow diagram was used to select articles, resulting in four eligible studies, which were critically appraised using the JBI Critical Appraisal Checklist. Results: All four reviewed studies reported that digital-based learning methods were more effective in improving BLS knowledge and skills among school students compared to conventional teaching methods. Conclusion: Various teaching methods have been proven effective in improving students’ knowledge and skills in BLS. Engaging and innovative training approaches can be considered as effective strategies for BLS education among school students.